Instigating and monitoring transdermal drug delivery using ultrasound-mediated cavitation - van Blokland, AC (2018)
Injections are a commonly used and widely accepted method of drug administration to prevent and treat diseases. Although using a needle and syringe provides a rapid, lowcost, and direct way of administering almost any kind of therapeutic agent into the body, it is a painful and invasive method leading to issues of patient compliance and needle–phobia. The delivery of drugs through the skin (transdermal delivery) is an attractive alternative approach because it is non-invasive and has low associated risks. However, the penetration of molecules into/through the skin is severely restricted by the outermost layer of the skin (stratum corneum). Initial studies of ultrasound-mediated, cavitation-enhanced transdermal drug delivery have shown great promise by utilising a gel formulation containing polymeric cavitation nuclei to help deliver a model immunogen (Ovalbumin) into the skin. However, enhanced adoption of this technology to permit delivery of several classes of therapeutic agents requires further validation and optimisation and is currently stymied by the lack of real-time monitoring when used across a broad range of therapeutic classes and environmental conditions. Such monitoring is especially important in situations where the dose of the delivered therapeutic agent needs to be precisely defined. Therefore, the focus of this thesis is to achieve transdermal delivery using cavitation-enhanced transport and develop methodologies to monitor or at least confirm successful delivery in real-time. [abstract continued in thesis]